Adsorpsi Ion Logam Pb Dengan Menggunakan Karbon Aktif Kulit Durian Yang Teraktivasi - Nuvicha Rizqi Yuniva Zikra; Chairul Chairul; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Lead (Pb) is purified so widely used by humans in a variety of activities. Environmental pollution by lead (Pb), mostly from human activities are extracting and exploiting these metals. One way to prevent environmental contamination that is the technique of adsorption using activated carbon from durian skin. Manufacture of activated carbon durian skin consists of sample preparation process, carbonization, activation with KOH, washing and sieving. Activated carbon durian skin with carbonization temperature 3200C for 2 hours, the activation is done by calcination at a temperature of 400oC for 2 hours with 0.1 N KOH activator and activated carbon filtration with a sieve size of 60, 80 and 100 mesh. From research conducted activated carbon has met the quality standards of quality according to SNI 06-3730-1995 activated carbon with a water concentration of 7.4%, 6.76% ash concentration, as well as the absorption of I2 solution of 576.95 mg/g. Activated carbon works very well in absorbing Pb where the sample was stirred with a speed of 140 rpm using the batch system. The contact time used after mixing is 60, 90 and 120 minutes. The size of the activated carbon from durian skin best for the entrapment of Pb is 100 mesh and 120 minutes contact time with the adsorbent adsorption efficiency reached 90.68%.Keywords: durian skin, adsorption, activated carbon, lead (Pb)